THE USE AND IMPACT OF GENERATIVE ARTIFICIAL INTELLIGENCE ON LEARNING AND ASSESSMENT - Inessa Vyacheslavovna Morkhova,Dmitry Denisovich Tulaganov (International Journal of Literature and Language Studies, 2026)
The use of generative artificial intelligence technologies in education has the potential to revolutionize learning and educational assessment by personalizing the learning experience, providing immediate feedback, and improving the overall learning experience. The relevance of the research is due to the spread of artificial intelligence technologies and the lack of practices for formative assessment of educational achievements in higher education.